Al-Qur’an Dan Ketenangan Jiwa: Mengungkap Dampaknya Pada Kesehatan Mental Siswa - Lazuardi, Kunzita; Usriyah, Lailatul (IJIT: Indonesian Journal of Islamic Teaching, 2025)
This study reveals how reading the Qur'an affects mental well-being. Readers experience inner peace and a deep sense of gratitude, an experience that is universal to those who understand its meaning. In line with the Qur'an, Surah Fussilat verse 44, the Qur'an is described as a healer for the soul, especially for those who read with faith, alleviating the unhappiness of the heart. This study aims to reveal the effects of reading the Qur'an on mental health, based on an interest in the therapeutic benefits of religious activities. Using surveys and interviews, a positive association was found between the habit of reading the Qur'an and improvements in mental health, including reduced stress and anxiety. These results highlight the potential of religion as a psychological support and suggest its integration into mental health approaches. Further research is needed to explore the mechanisms behind this and optimize interventions. Keyword: Study, Qur’an, Mental Health.